Methodology in an ecological framework: hearing parents voices on child home safety. (1st March 2011) - Simpson, J; Fougere, G; McGee, R; Jaye, C
Abstract : Measuring mortality, morbidity or controllable hazards, and determining risk factors are crucial starting points for developing interventions for child home injury. For programmes to work effectively however, an analysis of the contextual and personal interactions that operate in the home environment is also important. Preventing child injury at home is more than the implementation of a series of interventions, it is about safety management including coping with conflicting behaviours and beliefs, interactions between people and a dynamic environment. Primary carers, usually the parents, are key stakeholders in child safety and their perceptions, beliefs and actions are critical for safety management at home to be effective. Most parents want to keep their children safe, but unlike those who analyse at the population level, they work at a personal level that brings very different, but very valid, perspectives to the problem. Hearing the experiences, knowledge and opinions of these key practitioners regarding what influenced their safety management for young children is vital for the design, development and delivery of effective programmes to reduce home injury to young children. How to do so has been approached in various ways. This qualitative study undertook a series of in-depth interviews. This presentation describes and discusses methodological and practical aspects of developing the study, considerations in choosing methods for obtaining robust qualitative data and undertaking analyses, and issues that emerged with drawing conclusions for the design, development and delivery of prevention programmes.